Competitiveness of Knowledge in the Context of the Fourth Industrial Revolution - Prušević Sadović, Filduza R.; Šehović, Sefedin F.; Mandić, Danimir P. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Knowledge and ability represent the crucial requirements for an individual nowadays. Knowledgeable people find it easier to solve problems and overcome difficult situations. Knowledge is a valuable commodity in the modern world which, if updated regularly, never goes out of style or significance. The paper explores the concept of competitiveness of knowledge in the context of the Fourth Industrial Revolution and how it impacts an individual’s social and economic standing. As a result of the revolution, which is brought about by the development of digital and nanotechnology as well as artificial intelligence that permeates every aspect of a social being, new roles are imposed on individuals. The knowledge and skills that people should possess in today’s world are discussed, along with how they relate to technology advancements. Learning is the potential energy of a person capable of accepting rational needs as motivations and transforming them into actions through activity. Since everyone has a unique personality and learning is an individual act, everyone acquires knowledge in their own way. Learning occurs continuously throughout life, connects to all human endeavors, validates an individual’s resolve, and enables the selection of a value system and way of life. Throughout history, learning needs have changed, grown, and been greatly impacted by the social environment. The intersection of various learner characteristics with the situations that shape an individual’s life and interests is known as the culture of learning. To address problems with content presentation and learning style, an individual can shift from one form and method of learning to another, as well as from one location to another. We are discussing various learning patterns that point to the most successful, advantageous, and adaptable learning ranges. They represent the state of knowledge in the most significant spheres of life and action at any given time. They line up with societal norms. However, learning varies not only among individuals but also among societies, cultures, and civilizations. Science, education, learning, and knowledge are the most reliable foundations for the future. Changes that are more profound than any other in human history have resulted from the abrupt leap in social development and the evolution of the Third to the Fourth Industrial Revolutions. Thanks to digital media and the Internet, society is becoming a “global village” where information can be accessed in a split second. A person is exposed to a large amount of information every day and their working environment is ever-changing. Man is compelled to adjust to the new environment as modern means assume his roles. Being open to change and improvement throughout one’s life is one of the best ways to stay competitive in the labor and knowledge markets, if not the only one. Lifelong learning and being open to change and improvement are two, if not the only, ways that an individual can stay competitive in the labor and knowledge markets. Gone are the days when a person began and ended his career at the same place of employment. The imperatives of the modern era are the knowledge society and the learning society. They include the entire vertical of the educational system, the economy, and all social and economic structures. A society that prioritizes lifelong learning, makes learning content available, provides conditions for learning, and supports the individual to balance work and learning is essential in the modern world. To prepare today’s students for the workforce of the future and the society they will inhabit, it is imperative that the current educational systems be updated. This shift necessitates modifying the learning content to include the human and technical skills required to create inclusive, growing economies. To enable the creation of a comprehensive education system, significant changes can only take place if there is collaboration among education ministries, educators, and the private sector.